A pragmatic study of directive speech acts in the cartoon “Sadaqa Rasoul Allah” - Ali, Asem Shehadeh; Alqudah, Mohammad Ahmad; Zaki, Mawaddah Mohd (Journal of Arabic Language Sciences and Literature, 2023)
Pragmatics as one branch of linguistics is concerned with syntax, semantics, morphology, and phonology, which is the study of meanings conveyed by speakers and their interpretation by listeners; As for animation, it is among the factors influencing the formation of knowledge among children in many ways, such as perception, memory, attention, and language. One of the objectives of this study is to know the types of directive speech acts in the animated series “The Messenger of Allah has spoken the truth,” and to know the function of directive speech acts in the animated series. “The Messenger of Allah spoke the truth,” and the study follows the descriptive and analytical methodology. The conclusions of this study are: The description of directive speech acts was through the theory of Bach and Harnisch in the film of the animated series “The Messenger of Allah Believed”, and there are (109) directive speech acts, and that the functions of informative speech acts according to the theory of Bach and Harnisch reach (6) functions, which correspond to With the dialogue in a more clear way, and fifteen dialogues work with the type of verbs of requests, (53) dialogues work with the type of verbs of requirements, (6) dialogues work with the type of verbs of requirements, (2) dialogues work with the type of verbs of permission, (9) dialogues work with the type of verbs of prohibitions, (6) dialogues work with the type of verbs of advice, and it explains Statements are the type of questions frequently used in the cartoon “The Messenger of Allah has spoken the truth”.